Constitutional ring chromosomes and tumour suppressor genes. - Tommerup, N (1992)
The types of malignancy reported in carriers of constitutional ring chromosomes r(11), r(13), and r(22) are concordant with the chromosomal assignment of tumour suppressor loci associated with Wilms' tumour, retinoblastoma, and meningioma. It is suggested that the somatic instability of ring chromosomes may play a role in this association and that constitutional ring chromosomes may be a source for mapping of tumour suppressor loci with the potential for covering most or all of the human genome. The hypothesis predicts the presence of a locus on chromosome 10 associated with follicular carcinoma of the thyroid, in line with previous cytogenetic findings of rearrangements involving chromosome 10 in thyroid tumours, and a locus on chromosome 22 associated with testicular cancer. Development of neurofibromatoses (NF) that do not fulfil the clinical criteria of neurofibromatosis type 2 (NF2) in carriers with r(22) suggests either the presence of an additional NF locus on chromosome 22 or that ring chromosome mediated predisposition to somatic mutation of a specific tumour suppressor may be associated with atypical development of features usually associated with germline mutations.